Classroom teacher candidates' self-leadership behaviour - Semerci, Nuriye; Guney, Kaan; Alper-Ay, Ferda; Semerci, Cetin (Academic Journals, 2010)
The aim of this research is to determine classroom teacher candidates' self-leadership behaviour. The survey method is used in this research. The population of the research consisted of 272 senior students studying at the faculties of education at primary classroom teaching departments at four universities (Agri Ibrahim Cecen University, Cumhuriyet University, Firat University and Kilis 7 Aralik University) in Turkey. The sample of the research has randomly been chosen and consisted of 262 (83%) students. Statistically a meaningful difference at the 0.05 level is found when distributing the collected data about self-award and cueing, the sub-dimensions of the measure, to universities. The self-leadership behaviour has kept steady at the level of Generally and should be advanced to the level of Always.
Keywords: Self-seadership; self-leadership behaviour; classroom teacher candidates